Judicial Construction of Marital Disputes in Divorce Cases: Ratio Decidendi, Legal Certainty, and Justice in the Aceh Sharia Court - M. Rani; Mahdi Abdullah Syihab (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2026)
In its legal reasoning (ratio decidendi), the Aceh Shari’ah Court has been inconsistent in ruling on divorce cases concerning the interpretation of ‘continuous disputes and quarrels’ as provided for in Article 39 of the Marriage Act and Article 116(f) of the Islamic Law Code (KHI). This issue arises from the lack of clarity regarding the judicial parameters for determining what constitutes a marital conflict sufficient to justify divorce, which has the potential to lead to legal uncertainty and substantive injustice. The aim of this research is to analyze the judges’ reasoning in their judicial interpretation of divorce cases at the Aceh Sharia Court, with a view to realizing the principles of legal certainty and justice for the parties involved. This study employs a normative legal research approach using the case study method, analyzing selected divorce judgments from various jurisdictions in Aceh, supplemented by a comparative perspective. The findings reveal five dominant indicators used by judges: domestic violence (physical and psychological), polygamy without consent, prolonged separation, ongoing conflict, and the doctrine of a broken marriage. However, the formulation of these indicators remains descriptive and lacks standardized judicial benchmarks, thereby creating a tension between procedural legal certainty and substantive justice. From an academic perspective, this study contributes by formulating a typology of indicators of matrimonial disputes in Islamic court jurisprudence and proposing a structured framework to harmonize legal certainty with maqāṣid-oriented justice in divorce courts.